Peran Guru dalam Penegakan Nilai-Nilai Hak Asasi Manusia pada Peserta Didik di Sekolah - Hendrikus Otniel Nasozaro Harefa; Deprianus Waruwu; Perdamaian Zega; Berlin Syahputra Harefa; Arisman Jaya Zendrato; Septiman Christian Gea; Wanson Karunia Gea (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The purpose of this study is to determine the implementation and role of teachers in enforcing human rights values (HAM) to students in schools. with a historical-normative approach through literature and document analysis, in order to trace the historical construction and normative meaning of human rights values. The results of the study are that the role of teachers is very important in addition to the role of the parents of the students themselves. Teachers have implemented the implementation of human rights values to students in learning well, teachers have provided students with good education, attention to students, facilitate learning, and care. And the role of teachers in enforcing human rights to students is to participate in learning, because learning can include human rights values, especially in civic education learning, which is expected to enable students to apply Pancasila values in life. Teachers must also have a dynamic nature and quickly follow the developments of the times so that students become good and smart citizens.